Cardioncological Approach for Trastuzumab Therapy in Breast Cancer Patients With Cardiotoxicity: Impact on Adherence and Clinical Outcome - Fabiani, Iacopo; Cipolla, Carlo Maria; Colombo, Nicola; Cardinale, Daniela (Frontiers in Pharmacology, 2020)
Background Treatment with Trastuzumab is associated with cardiotoxicity. If Trastuzumab could be administered in a safe manner to patients who develop a reduced left ventricular ejection fraction (EF) of < 50% remains poorly understood. Objective To evaluate the impact of a cardioncological approach in terms of adherence and continuation of oncological therapy with Trastuzumab. Methods and Results Internal databases of candidates for trastuzumab chemotherapy with evidence of cardiotoxicity according to echocardiographic criteria were retrospectively evaluated. Eighty-four female patients (age 51.7 years, 95% CI 49.5 – 53.8), were finally included. Patients were divided to receive a standard (n 27) or cardioncological (n 57) scheme. Baseline EF values were within normal limits (60.9, 95% CI 60 - 61.9%; p=0.5 between groups). The nadir of EF observed during trastuzumab therapy was more pronounced in the standard care group (40.6, 95% CI 37.3 - 43.9% vs. 46.3, 95% CI 44.3 - 48.3%; p=0.002). At re-challenge, after cardiotoxicity detection, all patients in the cardioncological arm resumed and completed trastuzumab therapy (p<0.0001). An overall reduction of EF was observed at the final evaluation (p <0.0001 vs baseline). Cardioncological approach was the only independent determinant of ΔEF from baseline to final evaluation (R20.12; p=0.004). We observed a total of 13 (15%) HF events, 7 (26%) in the standard and 6 (10%) in the cardioncological approach group (p =0.1). Patients in the cardioncological approach arm had a better outcome (Log Rank Chi-squared 4.89; p=0.02). Conclusions A targeted cardioncological approach, in patients with evidence of cardiotoxicity during HER-2 inhibitor therapy, could favorably influence the oncological management of breast cancer patients, reducing the adverse cardiovascular impact of chemotherapy.